Ordem econômica e política nacional de recursos hídricos: hermenêutica constitucional para o desenvolvimento sustentável - Guimarães, Patrícia Borba Vilar (2008)
This research proposes a study about the interpretative techniques application that are compatible with the national legal system under the principles for Sustainable Development characterized in Brazilian Constitution. It verifies the actual possibility of reconciliation between national development and environment protection, with reflections under the water legal protection. It was proposed, therefore, to point subsidies for jurisdictional decisions involving development and the environmental goods, protected as constitutionally guaranteed principles. It was assumed that, both development and environment protection represents basic rights that are eventually placed in conflict situations, considering the many legitimate economic activities within the Brazilian State. A representative case analysis was elected within the current national scene, detailing the judicial and political conflict involving the Transboundery water Project from the São Francisco River Basin to another Northeastern river basin in Brazil. The implementation of several constitutional principles with elements from legal hermeneutics provides subsidies for the legal analysis about the conflict between development and environmental protection. It was assumed that the main discussion item about rights due to development today is the institutions influence and their results, among them the rules, laws and interpretative elements for the constitutional text objectivity, as the institutions credibility and the Supreme Courts interpretations. The use of interpretative resources for specific conflict situations about constitutional principles by Superior Courts, on the search, would bring a contributory factor for decision safety, related to sustainable development principles, elimination of inequalities and regional protecting for the environment. Specific aspects of Law No. 9.433/97 that introduced the National Water Resources Policy were examined, with its instruments, in order to specifically contextualize aspects of the Brazilian water resources management politics